(untitled) (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Autologous blood patching (ABP) has been described as a modality of treatment of bronchopleural fistulas (BPF). The success rates have varied chiefly because the numbers studied have been small and the populations inhomogeneous. We conducted this study to determine the success rate in patients with BPF of spontaneous onset. Methods: All patients with spontaneous pneumothorax with no evidence of pleural infection and in whom the air leak did not subside despite 48 hours of conservative management were included These patients underwent one to three episodes of blood patching in 50ml aliquots. Demographic profile, smoking status, success rate and complications were recorded and compared. Results: Between July 2011 and January 2014, seventy-six patients underwent ABP. The overall success rate of ABP was 58%. Twenty one were successful in first attempt (27.6%), a further 12/55 (22%) in the second and 11/43 (25%) in third attempt. The success rates did not differ significantly with etiology of spontaneous pneumothorax (P = 0.706); smoking status (P value = 0.958); duration of air leak prior to ABP (P= 0.149) and presence of residual pneumothorax after chest tube insertion (P= 0.176). Seven complications (3 pleural infections, 1 surgical emphysema, 1 expansion of pneumothorax and 2 recurrence) occurred. Infectious complications occurred in patients who received two or more instillations of blood. Conclusion: ABP achieved a modest success rates in our experience. Two or more attempts may be necessary to attain a successful result but one has to be mindful of the possibility of infection. Journal of Society of Surgeons of Nepal, 2015; 18 (2)